The dual Syk/JAK inhibitor cerdulatinib antagonises B-cell receptor and microenvironmental signaling in chronic lymphocytic leukemia - Blunt, Matthew D (Clin Cancer Res, 2016)
PURPOSE: B-cell receptor (BCR)-associated kinase inhibitors such as ibrutinib have revolutionised the treatment of chronic lymphocytic leukemia (CLL). However, these agents are not curative and resistance is already emerging in a proportion of patients. Interleukin-4 (IL-4), expressed in CLL lymph nodes, can augment BCR-signalling and reduce the effectiveness of BCR-kinase inhibitors. Therefore simultaneous targeting of the IL-4- and BCR-signalling pathways by cerdulatinib, a novel dual Syk/JAK inhibitor currently in clinical trials (NCT01994382), may improve treatment responses in patients. EXPERIMENTAL DESIGN: PBMCs from CLL patients were treated with cerdulatinib alone or in combination with venetoclax. Cell death, chemokine and cell signalling assay were performed and analysed by flow cytometry, immunoblotting, Q-PCR and ELISA as indicated. RESULTS: At concentrations achievable in patients, cerdulatinib inhibited BCR- and IL-4-induced downstream signalling in CLL cells using multiple read-outs and prevented anti-IgM- and nurse-like cell (NLC)-mediated CCL3/CCL4 production. Cerdulatinib induced apoptosis of CLL cells, in a time- and concentration-dependent manner, and particularly in IGHV unmutated samples with greater BCR-signalling capacity and response to IL-4, or samples expressing higher levels of sIgM, CD49d+ or ZAP70+. Cerdulatinib overcame anti-IgM, IL-4/CD40L or NLC-mediated protection by preventing upregulation of MCL-1- and BCL-X(L), however BCL-2 expression was unaffected. Furthermore in samples treated with IL-4/CD40L, cerdulatinib synergised with venetoclax in vitro to induce greater apoptosis than either drug alone. CONCLUSION: Cerdulatinib is a promising therapeutic for the treatment of CLL either alone or in combination with venetoclax, with the potential to target critical survival pathways in this currently incurable disease.